Keunggulan Bersaing dan Kepeloporan Teknologi - Laoh, Sinjo James (JBE (Journal of Business and Economics); Volume 9 No.1, 2010 JBE UNKLAB, 2010)
Pioneering in technology, creating products that can be accepted well by the market is a long term strategy for a company’s survival and continued existence.  That goal can be attained successfully if the company possesses competent management skill and strategic goals.  Without managerial skill, such as brilliant and resourceful management, pioneering would not contribute significantly to the company.  It would be similar to an unplanned expedition to penetrate a very competitive market.  Technological Pioneering accompanied by appropriate planning, and supported by the right structure and effective market plans, will position the company as a market leader.  But this endeavor requires great cost and risk, that will not always result in growth and profit.